Discrimination against Women in Accessing Higher Education in Cambodia - Sophorn Tuy (Journal of Southeast Asian Human Rights, 2019)
Young women in Cambodia face challenges in accessing higher education. Social norms, financial constraints and other problems are the main root causes in the limitation of opportunities for women to pursue higher education. Social norms of the older generation in Cambodia remain from the past and they often think that it is not necessary for women to study in higher education institutions since a women’s role is to just be a housewife after marriage. Another restriction on women’s access to higher education is that they often have financial problems in supporting their education. Some women have to work in order to support their families, so they have no chance to pursue a higher education. Additionally, since most universities are located in cities, parents often feel insecure about their daughters studying far away from home. Currently there is increased enrollment of young women in higher education due to Government action, as it has ratified international conventions and enacted domestic laws. As well, there is government cooperation with NGOs to establish some strategies and action plans to promote and protect gender equality in all sectors, including the education sector, by improving scholarship opportunities or building dormitories for female students to live in while studying at university. However, these supports cannot provide access to higher education for young women in all areas in the Kingdom of Cambodia, and Cambodia has not yet enacted specific laws to promote the participation of women in higher education. This research aims to explore the opportunities that have been provided to young women to pursue higher education, particularly at the university level. After exploring the opportunities, the researcher will analyze data regarding the challenges for women in accessing higher education. Finally, the researcher will provide some possible recommendations to address these challenges. This research utilized multiple methods, including desk review and structured interviews. Interviews were conducted face-to-face and in focus group discussions (FGD). Desk review focuses on all relevant international and national laws, strategic and action plans related to the promotion of women studying at university and the de facto equality of that issue.